STRATEGI PEMBIMBINGAN ORANG TUA KEPADA ANAK USIA SEKOLAH DASAR DALAM BERMEDIA SOSIAL YANG BIJAK - Misbahul Jannah; Shaleh Shaleh; Iva Nandya Atika (Jurnal keilmuan dan Kependidikan dasar, 2023)
The purpose of this study is to reveal parental guidance strategies for elementary school children in wise social media. This type of research is qualitative research using a descriptive approach. The data was obtained in this study using interviews and observation. This research was conducted in the village of Wawai substation located in Banjarmasin, South Kalimantan. This research was conducted in February-March 2023. In-depth interviews were conducted with 3 parents whose children attended Madrasah Ibtidaiyah Negeri 13 Hulu Sungai Tengah. The data collected was then analyzed using the Miles, Huberman, and Saldana models through the stages of condensing data, displaying data, and drawing conclusions. The formulation of the problem in this study is what are the strategies of parents in guiding their children to wise social media and the negative and positive impacts what happens in using social media itself. The results of this study indicate that elementary school-age children still need adequate supervision in using social media, so they can use it properly and correctly. Parents are influential figures in children's lives, for this reason, it is necessary to optimize their role as mentors in all areas of their children's lives, including in social media. The guidance strategy given by parents to their children for wise social media can be done by: (1) time management, namely setting time limits for using social media, (2) monitoring, namely parents accompanying, monitoring, and accompanying children when using social media, and (3) explanation, namely explaining to children what the benefits and risks are when using social media. There are 2 negative impacts of social media, they are addiction and lack of physical activity. While the 2 positive impacts are easy access to information and learning to be creative.